Saccharomyces cerevisiae Fermentation Product Did Not Attenuate Clinical Signs, but Psyllium Husk Has Protective Effects in a Murine Dextran Sulfate Sodium–Induced Colitis Model. Issue 11 (15th October 2020) - Lin, Ching-Yen; Lee, Anne H; Chiu, Karen K; Vieson, Miranda D; Steelman, Andrew J; Swanson, Kelly S
ABSTRACT: Background: Yeast products and psyllium husk may provide relief from clinical signs of colitis due to their ability to promote gut integrity, modulate gut microbiota, or positively affect immune responses, which have been demonstrated in several species. Objective: The objective of this study was to investigate the effects of a Saccharomyces cerevisiae fermentation product (SCFP) and psyllium husk (PH) on cecal and fecal microbiota, colonic gene expression and histopathology, and mesenteric lymph node (MLN) immune cells in a dextran sulfate sodium (DSS)–induced colitis model. Methods: Male C57BL/6J mice ( n = 54) were assigned to a control, 5% SCFP, or 5% PH diet. After 2 wk of diet adaptation, mice were provided distilled water or 3% (wt:vol) DSS for 5 d ad libitum. Body weight, food and water intakes, and disease activity index (DAI) were recorded daily during the treatment period. Fresh fecal samples were collected before and during treatment for microbial analyses. After treatment, mice were killed, followed by tissue collection. Tissues were stored in proper solutions until further analyses. Data were analyzed using the Mixed Models procedure of SAS 9.4 (SAS Institute). Results: Consumption of SCFP increased ( P < 0.05) species richness of the gut microbiota and relative abundance of Butyricicoccus in fecal and cecal samples compared with control or PH mice. PH mice had greater ( P < 0.05) gene expression of claudin ( Cldn ) 2, Cldn3, Cldn8, and occludin ( Ocln ) compared with control mice. DAI, MLN immune cell populations, colonic histopathology, and colonic gene expression were not affected ( P > 0.05) by SCFP in DSS mice. DSS mice consuming PH had lower ( P < 0.05) DAI compared with control or SCFP mice. Conclusions: Results suggest that, despite the modest changes it had on cecal and fecal microbiota, SCFP did not attenuate clinical signs associated with DSS-induced colitis in mice, while PH showed protective effects.